The role of RNA methylation in glioma progression: mechanisms, diagnostic implications, and therapeutic value - Zhang, Shao-Ze; Liu, Shao-Yan; Cheng, Meng-Die; Zhang, Yin-Feng; Tian, Jia-Wei (Frontiers in Immunology, 2025)
Glioma represents a highly lethal form of malignant tumour, with RNA methylation emerging as a critical regulator of its oncogenesis and progression. As a prevalent post-translational modification, methylation influences various biological functions, particularly RNA processing, by modulating splicing, transport, and degradation of both mRNAs and noncoding RNAs. Key methylation types such as N6-methyladenosine (m6A), N5-methylcytosine (m5C), N7-methylguanosine (m7G), and N1-methyladenosine (m1A) are dynamically regulated by specific enzymes known as writers, erasers, and readers. Dysregulation of these modifications contributes to glioma pathophysiology, while offering potential biomarkers for early detection and promising therapeutic targets. This review explores the mechanistic roles of RNA methylation in glioma and highlights its translational implications, aiming to advance molecular diagnostics and targeted interventions in glioma treatment.